2023
DOI: 10.1002/smll.202205488
|View full text |Cite
|
Sign up to set email alerts
|

Electricity‐Wettability Controlled Fast Transmission of Dopamine in Nanochannels

Abstract: Achieving fast transmembrane transmission of molecules in organisms is a challenging problem. Inspired by the transport of Dopmine (DA) in organisms, the DA transporter (DAT) binds to DA in a way that has a ring recognition (the recognition group is the tryptophan group). Herein, D‐Tryptophan‐pillar[5]arene (D‐Trp‐P5) functionalized conical nanochannel is constructed to achieve fast transmission of DA. The D‐Trp‐P5 functionalized nanochannel enables specific wettability recognition of DA molecules and has grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Similar behaviors have been reported in other systems. [68][69][70][71][72] Fig. 3 Scheme illustrating the implications of the variations in the (a) free volume and (b) surface wettability of the channel over the I-V curves.…”
Section: Wettabilitymentioning
confidence: 99%
“…Similar behaviors have been reported in other systems. [68][69][70][71][72] Fig. 3 Scheme illustrating the implications of the variations in the (a) free volume and (b) surface wettability of the channel over the I-V curves.…”
Section: Wettabilitymentioning
confidence: 99%
“…The experimental results showed that it is beneficial to transport negatively charged ATP in the ReÀ P6 channel, and the transport flux gradually increases with the increasing of applied positive voltage. [50][51][52][53][54] Among them, the mercapto ethylamine pillar [6]arene has a robust selective interaction with ATP, facilitating ATP to enter the ReÀ P6-channel. Meanwhile, the departure of ATP in the sub-nanochannel also requires an additional driving force to promote ATP to leave the membrane of the ReÀ P6-channel.…”
mentioning
confidence: 99%